Glucose gasification in super-critical water conditions for both syngas production and green chemicals with a continuous process. (June 2016) - Molino, A.; Migliori, M.; Macrì, D.; Valerio, V.; Villone, A.; Nanna, F.; Iovane, P.; Marino, T.
Abstract: The paper reports on experiments of glucose gasification with water in supercritical conditions (SCW). The adoption of these process conditions revealed advantages in terms of biomass conversion efficiency as the resulting liquid phase includes some important compounds (Acetic Acid, 5-HFM, furfurals). In addition the high operative pressures allow either to consider the possibility to use this technology inside the steam cycle in order to produce power and liquid/gaseous biofuels such as synthetic natural gas and/or methanol/DME(di methyl ether). In fact, from the experimental tests, it was possible to evaluate that using glucose, that is the main intermedia of SCW gasification from wet biomass, is possible to estimate a syngas production of about 100 lt – 200 lt for each kg of glucose fed, while the global gasification efficiency was of about 10–18%. Syngas product to SCWG has been analysed and the main results shows that, in the range investigated, CO content was 40–50%vol., H2 10–15%, CH4 10–20%, C2 +2–8% and at the end CO2 with a volume content of about 20–30% and then with lower calorific value of about 20 MJ/Nm 3 . Analysis on the liquid phase was carried out and the main results has been an high production of both 5-hydromethil furfural and 2-Furaldehyde that have a great potential as "carbon-neutral" feedstock for fuels and green chemicals. Highlights: Glucose gasification in Supercritical conditions for syngas and chemicals production. Energy recovery from biomass. Bio-based production from thermochemical processes.